The implementation of aboriginal people act 1954 (Act 134) and customary law in the appointment of Tok Batin Kaum Jakun in Bekok, Segamat / Alizah Ali, Rohani Jangga and Ahmad Nawawi Yaakob - Ali, Alizah; Jangga, Rohani; Yaakob, Ahmad Nawawi (Universiti Teknologi MARA Cawangan Pahang, 2020)
There are not many studies done on the guidelines that must be followed when an appointment for a new Aborigine tribe leader is to be implemented. Besides customary laws, there are also legal guidelines that must be adhere to. So, the present study purpose looks into the implementation of both customary law and the Aboriginal People Act 1954 in the issue of appointment of Tok Batin Orang Asli Jakun in Bekok, Segamat, A series of interviews were carried out for this fundamental study. Related information from books, articles, magazines, previous studies are used and supported by various case study and legal provision. The main findings are both customary law and the Aboriginal People Act 1954 complement each other and there is no contradiction between them. The Act provides the general application of appointment of a Tok Batin while the customary law discusses on the qualification, vote system, the ceremony to welcome the new Tok Batin and others. The study contributes to information about legal and customary procedures when appointing a selected Aborigine tribe leader.